PENGARUH GADGED PADA ANAK USIA DINI: THE INFLUENCE OF GADGETS ON EARLY CHILDHOOD - Sulyandari, Ari Kusuma (Universitas Islam Malang, 2019)
Many people are already using gadgets. Not just adults and teenagers. Children also use gadgets. Gadgets can not be avoided due to technological advances in modern times. Many people use gadgets, so kids come to use them. Because children imitate what they see. Many apps on the gadget draw people to use it. Easy internet connection, multiply gadget users. Wearing gadgets for a long time and without parental supervision, brings a bad impact for young children. Gadged psychologically disturbing and causing tantrums. not only psychological, physical health is also disrupted because of the gadget. wearing gadgets at a long time affect eye health. Not only bad effects, gadgets also have a good impact on child development. Wearing gadget apps as well as interactive vidio, beneficial to the child's cognitive development. Parents should be selective and think again to give gadgets to children. Parental supervision and not spending time using gadgets, have a good and beneficial impact on early childhood users